Penerapan Kebudayaan pada Pembatas Ruang Tawing Halat pada Rumah Tradisional Bubungan Tinggi - Liritantri, Widyanesti; Febriani, Ghesti Fuji; Safitri, Adelin; Ramadhani, Azizatulatifah Permata; Azzahra, Nadine Putri; Pakpahan, Helena Elysabet (Waca Cipta Ruang, 2022)
Indonesia is famous for its diverse cultures, such as traditional houses in every region, each with its own uniqueness. One of which is in South Kalimantan, which possesses 11 types of Banjar traditional houses based on specific functions and certain social statuses, including the Bubungan Tinggi traditional house. The key feature of the Bubungan Tinggi traditional house is Tawing halat, which represents the identity of the family that lives in it. Tawing halat is a divider that separates public space and private space. In the Bubungan Tinggi traditional house, the Tawing halat’s presence is not only as a divider, but it also has historical value, an owner’s identity, and other purposes that make Tawing halat an important interior element, and its presence cannot be abandoned until today. This research aims to identify the purpose of Tawing halat in Bubungan Tinggi traditional house as an interior element that describes the cultural value and religion that thrives within the Banjar, South Kalimantan community. The method used is a qualitative descriptive method. The steps are collecting visual data of Tawing halat, then linking them with cultural values. It is hoped that this research can be a source of reference and knowledge for the community in preserving traditional culture through today’s architectural and interior design. Keywords: traditional house, interior, bubungan tinggi, culture, tawing halat, visual elements, south kalimantan